ANALISIS PENGARUH IKLIM ORGANISASI, KOMPETENSI KARYAWAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN ADMINISTRASI DI PT. AIR MANCUR SURAKARTA - Anari, Sahar; Rohwiyati, Rohwiyati (Universitas Of Surakarta, 2020)
In this study the author has the objective to determine the effect of organizational climate, employee competence, and motivation on the performance of employees in PT. Air Mancur Surakarta either partially or simultaneously. The hypothesis in this study are: Suspected organizational climate, employee competence, and motivation have significant effect on the performance of employees in PT. Air Mancur Surakarta either partially or simultaneously. The data required in this research is primary data obtained from questionnaires distributed to respondents. The analysis technique used in this study using multiple linear regression, t test, F test and test the coefficient of determination. Results of data analysis in this study it can be concluded that the organizational climate, employee competence, and motivation have significant effect on the performance of employees in PT. Air Mancur Surakarta either partially or simultaneously.